2009
DOI: 10.1007/s10681-009-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiant frost tolerance in pulse crops—a review

Abstract: Radiant frost is a major abiotic stress, and one of the principal limiting factors for agricultural production worldwide, including Australia. Legumes, including field pea, faba bean, lentil and chickpea, are very sensitive to chilling and freezing temperatures, particularly at the flowering, early pod formation and seed filling stages. Radiant frost events occur when plants and soil absorb the sunlight during the day time and radiate heat during the night when the sky is clear and the air is still. Dense chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…Question 4.2 is focused on a potential ecological advantage conferred by the ice-nucleation phenotype. Ice nucleation plays an important role in frost injury in crops ( [122][123][124][125][126]; reviewed by [127]), and bacteria expressing ice-nucleating proteins may have a selective advantage as plant pathogens [108]. Ice-nucleating strains of Fusarium avenaceum [105] occupy a similar ecological niche (overwintering in cereal residues, and causing disease in small grains [128]) as non ice-nucleating strains of Fusarium graminearum [105], but the ecological role of the persistence of the ice-nucleating phenotype in these strains are presently unknown.…”
Section: Identifying and Quantifying Contributions Of Biological Ice mentioning
confidence: 99%
“…Question 4.2 is focused on a potential ecological advantage conferred by the ice-nucleation phenotype. Ice nucleation plays an important role in frost injury in crops ( [122][123][124][125][126]; reviewed by [127]), and bacteria expressing ice-nucleating proteins may have a selective advantage as plant pathogens [108]. Ice-nucleating strains of Fusarium avenaceum [105] occupy a similar ecological niche (overwintering in cereal residues, and causing disease in small grains [128]) as non ice-nucleating strains of Fusarium graminearum [105], but the ecological role of the persistence of the ice-nucleating phenotype in these strains are presently unknown.…”
Section: Identifying and Quantifying Contributions Of Biological Ice mentioning
confidence: 99%
“…The presence of frost during flowering increased blossom drop and reduced pod and grain yields (Table 3). Low temperatures occurred in the other environments during the vegetative stage when plants are more tolerant (Maqbool et al, 2010).…”
Section: Environmental Effectsmentioning
confidence: 99%
“…Thus, temperatures above 19 °C at the onset of flowering and approximately 24 °C during the grainfilling period decrease yield (Turpin et al, 2003;Ajam and Vazin, 2011). A complicating factor is the presence of frost at early flowering that could cause flower and pod abscission with a subsequent yield loss; frost also produces tissue necrosis in larger pods, which affects the quality of the harvested product (Maqbool et al, 2010). Some authors recommend early planting only if there is no frost in the area and/or when the growing cycle of the genotype allows flowering in a frost-free period.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature stress delays panicle emergence and heading in sorghum (Majora et al, 1982). Even crops inherently tolerant to low temperature do suffer from cold stress during flowering (Maqbool et al, 2010). As a consequence, sorghum cultivars produced more leaves (Hesketh et al, 1969;Quinby et al, 1973), delayed floral initiation (Caddel and Weibel, 1971;Quinby et al, 1973), and found to induce male sterility (Downes and Marshall, l97l;Singh, 1977) when grown under low temperatures.…”
Section: Floweringmentioning
confidence: 99%